KEPENTINGAN MALAYSIA MENOLAK MERATIFIKASI INTERNATIONAL CONVENTION ON THE ELIMINATION OF ALL FORMS OF RACIAL DISCRIMINASION (ICERD) - Chindy Rauna Ruchi; Saiman Pakpahan (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2022)
The purpose of this study is to find out the reasons for Malaysia's refusal to ratify ICERD. Malaysia's refusal to ratify International Conventions on the Elimination of All Forms of Racial Discrimination is a problem currently being faced by the Malaysian government. In fact, ratification of ICERD is considered as a step forward for a country to end racial discrimination. The research methodology used is descriptive method with a ualitative approach and is carried out by means of literature study. The source of data used in writing this thesis is secondary data on all forms of publication regarding ICERD and discrimination in Malaysia, be it books, articles, journals, authoritative websites and local Malaysian newspapers. The results of the research show that, the reason for the rejection of ICERD ratification is because the international convention is considered to be contrary to the federal Constitution in article 153 and threatens the privileges of the indigenous people of Malaysia and contradicts the social contracts made by the rulers since the journey towards Malaysian independence. Keywords: Racial Discrimination, ICERD, Federal Constitution, Malaysia.